DC-CTL targeting carbonic anhydrase IX gene combined with iAPA therapy in the treatment of renal cell carcinoma. Issue 11 (2nd November 2021) - Ma, Heran; Tan, Yi; Wen, Dingke; Qu, Na; Kong, Qunfang; Li, Kun; Ma, Suxia; Zhang, Jianhui
ABSTRACT: Introduction: To deliver specific antigens in tumor immunotherapy, tumor cell lysates are commonly used to sensitize dendritic cells (DCs). However, the lysates possess low immunogenicity and contain many types of non-tumor-related antigens, which may induce autoimmune diseases. Tumor antigen peptides can provide high specificity but are expensive and their short half-lives limit their clinical application. Methods: In this study, we used adenovirus to transfer the carbonic anhydrase IX (CA9) gene into DCs to generate specificity to renal cell carcinoma (RCC) which is the most common space-occupying lesion in humans. Inhibition of antigen presentation attenuators (iAPA) technology was also used to enhance the DC delivery capacity. Finally, DCs were co-cultured with cytotoxic T-lymphocytes (CTLs) and the anti-tumor effects were evaluated. Results: The results showed that the CA9-DC-CTLs possessed a high specificity to CA9-positive cells and showed stronger anti-tumor activity than GFP-DC-CTLs both in vitro and in vivo . Discussion: These findings may suggest a novel treatment option for RCC.